2020
DOI: 10.3390/molecules25071496
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Lactoferrin Is Related with Dynamics of Neutrophils in Bacterial Infected Mice Intestine

Abstract: Lactoferrin (Lf) is a conserved iron-binding glycoprotein with antimicrobial activity, which is present in secretions that recover mucosal sites regarded as portals of invaded pathogens. Although numerous studies have focused on exogenous Lf, little is known about its expression of endogenous Lf upon bacterial infection. In this study, we investigated the distribution of Lf in mice intestine during Escherichia coli (E. coli) K88 infection. PCR and immunohistology staining showed that mRNA levels of Lf signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
1
0
2
Order By: Relevance
“…Previous study indicated that distribution of LF in mice intestine during E. coli K88 infection was upregulated in duodenum, ileum, and colon, but reduced in jejunum, by using PCR and immunohistology staining. These data pave the way for a better understanding of the key role of LF in intestine mucosal immune ( 104 ). A large number of studies have reported that LF regulates mucosal immune and targets the mechanism that induce inflammation ( 105 ).…”
Section: Immunomodulatory Role Of Lactoferrin In Intestine Mucosal Immune Systemmentioning
confidence: 89%
“…Previous study indicated that distribution of LF in mice intestine during E. coli K88 infection was upregulated in duodenum, ileum, and colon, but reduced in jejunum, by using PCR and immunohistology staining. These data pave the way for a better understanding of the key role of LF in intestine mucosal immune ( 104 ). A large number of studies have reported that LF regulates mucosal immune and targets the mechanism that induce inflammation ( 105 ).…”
Section: Immunomodulatory Role Of Lactoferrin In Intestine Mucosal Immune Systemmentioning
confidence: 89%
“…Laktoferyna występuje naturalnie w przewodzie pokarmowym ssaków. Ekspresję genu dla LF przez komórki nabłonkowe błony śluzowej potwierdzono, jak dotąd, w dwunastnicy odsadzonych prosiąt [90] oraz dwunastnicy, jelicie czczym, krętym i okrężnicy myszy [50]. Podczas zakażenia/zapalenia jelita wytwarzanie LF lokalnie znacznie wzrasta, co odzwierciedla zarówno jej większą syntezę przez komórki nabłonkowe jelita, jak i uwalnianie przez naciekające śluzówkę neutrofile [50].…”
Section: Laktoferyna W Przewodzie Pokarmowymunclassified
“…Ekspresję genu dla LF przez komórki nabłonkowe błony śluzowej potwierdzono, jak dotąd, w dwunastnicy odsadzonych prosiąt [90] oraz dwunastnicy, jelicie czczym, krętym i okrężnicy myszy [50]. Podczas zakażenia/zapalenia jelita wytwarzanie LF lokalnie znacznie wzrasta, co odzwierciedla zarówno jej większą syntezę przez komórki nabłonkowe jelita, jak i uwalnianie przez naciekające śluzówkę neutrofile [50]. W dotychczasowych badaniach poziomy LF w kale dobrze korelowały nie tylko z nasileniem choroby, ale też skutecznością leczenia przewlekłych nieswoistych chorób zapalnych jelita (wrzodziejącego zapalenia jelita grubego i choroby Crohna), co sugeruje, że w przyszłości takie oznaczenia mogą być rutynowo stosowane w ocenie stanu tych pacjentów [48].…”
Section: Laktoferyna W Przewodzie Pokarmowymunclassified